Characteristics of General Pathological Processes in the Lungs Following Clozapine Poisoning - O. L. Romanova; D. V. Sundukov; A. M. Golubev; M. L. Blagonravov; M. A. Golubev (Общая реаниматология)
The aim of the study: to study general pathological processes in the lungs in different time after acute clozapine and combined clozapine+ethanol poisonings.Materials and methods. The experiments were performed on 25 outbreed male rats. The animals were divided into 5 groups: 1) reference (intact rats); 2) clozapine poisoning, 3 hours; 3) clozapine poisoning, 24 hours; 4) combined clozapine and ethanol poisoning, 3 hours; 5) combined clozapine and ethanol poisoning, 24 hours. Clozapine was administered orally at a dosage of 150 milligrams per kilogram of the animal weight under anesthesia (chlorolase); alcohol was administered with clozapine orally at a dosage of 5 milliliters per kilogram of the animal weight. Animals of all these groups sacrificed by decapitation. Lung tissue samples were examined by light microscopy using a microscope Nikon Eclipse E-400 with a video system based on camera Watec 221S (Japan) at a 400X magnification. We evaluated the presence of the following signs: circulatory disturbances (hyperemia, hemorrhage), presence of atelectasis and dystelectasis, emphysema, cellular response (increased white blood cells count), desquamation of epithelium into the lumen of the bronchi, sludge. A morphometric analysis was performed using a grid developed by G. G. Avtandilov. The following signs were evaluated (volume percent, vol.%): the area of the alveoli, intraalveolar septi, vessels, white blood cells, the percentage of white blood cells in the intraalveolar septi , the area of the edema and dystelectasis.Results. the following histologic signs were found 3 hours after clozapine poisoning: desquamation of epithelium into the lumen of the bronchi; cellular response (increased white blood cells count); presence of atelectasis and dystelectasis; thickening of intraaveolar septi due to edema; infiltration of intraalveolar septi by WBCs. Atelectasis and dystelectasis in pulmonary parenchyma and infiltration with WBC were observed 24 hours after clozapine poisoning. In the group of animals treated with ethanol and clozapine and decapitated 3 hours after the poisoning the following histological signs were detected: desquamation of epithelium into the lumen of the bronchi, the secret in the lumen of the bronchi, cellular response, atelectasis and dystelectasis, perivenular hemorrhages, hemorrhages into the alveoli, hemorrhages into intraalveolar septi, dilation of the lumen of the bronchi, the presence of sludge, thickening of intraalveolar septi (due to infiltration with WBCs, detachment of the endothelium in blood vessels. Arterial hyperemia, cellular response (increased of WBC count), atelectasis and dystelectasis, and thickening of intraalveolar septi were found 24 hours after combined ethanol and clozapine poisoning. In all study groups the lumen of the alveoli was significantly smaller as compared to the reference group, but the area of the intraalveolar tissue, on the contrary, was significantly greater. The total area of pulmonary microvessels did not differ significantly from the reference group 3 hours after clozapine poisoning. It became significantly higher 24 hours after the poisoning. A significant increase in this parameter vs. the reference group was found both 3 and 24 hours after the administration of the combination of clozapine with ethanol by animals.Conclusion. In clozapine and clozapine + ethanol poisoning, a certain complex of general pathological processes in lungs develops. There are alteration of bronchial epithelium and the vascular endothelium, circulatory disorder, increased vascular permeability, infiltration of intraaveolar septis. Morphological and immunoreactive changes can be used for valuation of severity of general pathological process in acute clozapine and clozapine + ethanol poisonings and determination of the exact time of the poisonings.